An animal model of clinical kinetic analyzed to diminazene aceturate in subjects with Tripanosoma infection (Faculty of Medicine Universitas Indonesia, 2006)
Diminazene aceturate has been reported to inhibit the reverse transcriptase activity by intercalating action mechanism of a number of protozoon eucaryot parasitic like Trypanosoma species. The phamacokinetics of diminazene in the blood plasma of five infected goats treated with single intramuscular doses of 7 mg diminazen base kg-1 body weight was investigated. The concentrations of the drug were determined by reverse phase high performance liquid chromatography. Results show that the mean (± SD) Absorption, Distribution, Metabolism and Excretion (ADME) of the drug plasma followed a tri-exponential process with Ka (minutes-1) were obtained at 5.10-2 ± 26.10-3, α (minutes-1), K12 (minutes-1) and K21 (minutes-1) were obtained at 18.10-3 ± 1.10-2, 14.10-3 ± 1.10-2 and 1.10-3 ± 1.10-3. The mean values of β (minutes-1) and K13 (minutes-1) were obtained at 1.4.10-4 ± 4. 10-5 and 3.10-3 ± 2.10-3. The mean values of Tmax (minutes) and Cmax (µg.ml-1) were obtained at 53.71 ± 30.61 and 13.40 ± 8.13. The mean values of Vds (L), Cl (ml.minutes-1), T1/2β (hours-1) and AUC (µg.L-1.minutes) were obtained at 4.91 ± 3.12, 14.29 ± 4.08, 94.91 ± 33.23 and 12.680 ± 2.722. (Med J Indones 2006; 15:69-73)